The Impact of Nutritional Counseling on Complementary Feeding Practice and Infant Nutritional Status at Pakan Rabaa Solok Selatan Health Centre in Indonesia - Maidelwita, Yani; Sansuwito, Tukimin bin; Arifin, Yulia; Poddar, Sandeep (The Malaysian Journal of Nursing (MJN), 2022)
Introduction: Malnutrition in infants is not only caused by food shortages. There are some other factors that cause inadequacy in the provision of complementary feeding. According to previous research findings, malnutrition in infants and children is caused by the practise of providing complementary foods and mothers' ignorance about the benefits and proper way of breastfeeding, which influences the maternal attitude toward breastfeeding provision. The aim of this study was to determine the effect of counseling with a demonstration of the practice of complementary feeding on the nutritional condition of infants aged 6–12 months. Methods: This research is quasi-experimental research designed with a control group pretest and posttest. The study was conducted at the Health Center Pakan Rabaa Solok Selatan. This study was conducted from July-September 2020. Results: Before nutritional counselling practice, both groups' scores differed by 0.21 points, whereas after counselling practice, the difference between the control and intervention groups' scores is 0.52 points. Between the intervention and control groups, there was no significant difference in birth weight. Conclusion: The study found that there are significant differences between the nutritional counseling and demonstration with conventional nutritional counseling. So health centre should conduct nutrition education and demonstrations to improve the knowledge of breastfeeding regularly for the public as well as mothers whose education levels are low.